Stress Among Psychologist Candidates - Arini Rachmawati; Zainil Abidin (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
There were five participants in this study. The results indicate that the majority of participants showed negative emotional reactions, such as increased anxiety leading to a desire to avoid academic situations. Physical reactions also emerged, such as fatigue, sleep disturbances, and headaches. Some participants attempted to cope with stress by engaging in enjoyable activities or exercising, but some still struggled to cope with stressful conditions and felt desperate about academic demands. A psychology graduate must complete a professional psychology education program to be considered a psychologist. The existence of several requirements and responsibilities to be fulfilled in pursuing education as a psychologist candidate, along with obligations outside the academic scope, can increase the risk of stress. This research is a descriptive qualitative study aimed at illustrating the stress experienced among psychologist candidates. The participants in this study were five graduate students from various universities enrolled in a Master of Professional Psychology program. The research instrument used in this study was an interview guide based on the Perceived Stress Scale (PSS) questionnaire and the data analysis method applied was thematic analysis. The results showed that overall, the participants perceived the demands they faced as psychologist candidates to be stressful situations. Stress reactions included the emergence of negative emotions such as increased anxiety, as well as physical reactions such as fatigue, sleep disturbances, and headaches. Some participants attempted to cope with stress by engaging in enjoyable activities or exercising. However, some participants still had difficulty managing their stress, leading to feelings of hopelessness regarding academic demands. The findings of this study are expected to serve as a reference in developing intervention programs to address stress, particularly among students in professional psychology programs.Sarjana psikologi harus menyelesaikan program pendidikan profesi psikologi untuk dapat dikatakan sebagai psikolog. Adanya sejumlah persyaratan dan tanggung jawab yang harus dipenuhi dalam mengikuti pendidikan sebagai calon psikolog, bersama dengan kewajiban di luar lingkup akademis, dapat meningkatkan risiko stres. Penelitian ini merupakan penelitian kualitatif deskriptif dengan tujuan untuk menjelaskan gambaran stres pada calon psikolog. Partisipan dalam penelitian ini berjumlah lima orang mahasiswa Magister Psikologi Profesi dari beberapa universitas. Instrumen penelitian yang digunakan dalam penelitian ini adalah panduan wawancara yang disusun berdasarkan pada kuesioner Perceived Stress Scale (PSS) dan metode analisis data yang diterapkan dalam penelitian ini adalah analisis tematik (thematic analysis). Hasil penelitian menunjukan bahwa secara keseluruhan, para partisipan mempersepsikan tuntutan yang mereka hadapi sebagai calon psikolog merupakan situasi yang memicu terjadinya stres. Muncul reaksi stres berupa adanya emosi negatif seperti kecemasan yang meningkat dan juga terdapat reaksi fisik seperti kelelahan, gangguan tidur, serta sakit kepala. Beberapa partisipan mencoba mengatasi stres dengan melakukan kegiatan yang digemari atau dengan berolahraga. Namun, sebagian partisipan masih mengalami kesulitan dalam mengatasi kondisi stres tersebut hingga memunculkan perasaan putus asa terhadap tuntutan akademis. Temuan penelitian ini diharapkan dapat menjadi referensi dalam pengembangan program intervensi untuk mengatasi stres, khususnya di kalangan mahasiswa program pendidikan profesi psikologi.